Trissomia parcial do 13q: relato de caso atendido no Serviço de Crescimento e Desenvolvimento Caminhar do Hospital Universitário Bettina Ferro de Souza - FREITAS, Camila Spencer do Nascimento (2018)
Trisomy is the most common finding in cases of chromosomal abnormalities, the most important represented by chromosomes 21, 18 and 13.Trisomy 13 is full of severe condition is rare survival of patients after the first year of life. In this report we described an unusual type trisomy, partial trisomy of 13q in a patient treated at the Genetics Clinic of the Department of Growth and Development, University Hospital Bettina Ferro de Souza, presenting the clinical characteristics and comorbidities of this genetic disorder. The report was conducted through interviews with the head of the patient, physical examination and chart review, and obtaining photographic record. Among the clinical stand out microcephaly, microphthalmia, typical facies, chest deformity and limb, respiratory disorders, kidney and neurological consistent with literature. Conducted multidisciplinary follow with effective control of the clinical problems presented, a fact relevant to patient survival.